PERAN DAN FUNGSI MAHKAMAH SYAR’IYAH TERHADAP PERLINDUNGAN HAK PEREMPUAN DALAM PERCERAIAN - Dian Eriani; Teuku Nazaruddin; Yusrizal Yusrizal (Program Studi Magister Hukum Universitas Malikussaleh, 2021)
The authority of the Syar'iyah Court in the field of marriage has a lot of contact with the interests of women. The decisions made from these cases are expected to be able to fulfill women's rights in return for the perceived suffering. Has the Syar'iyah Court already played a role and function in its decisions and consideration has been gender responsiveness to protect women's rights. Specifically the rights of women arising from divorce, in the verdict and the rights of civil servants' wives due to divorce divorce. This study aims to determine the role of the Syar'iyah Court in protecting the rights of women in divorce through its decision. The method used is juridical normative with the conceptual approach and the statute approach. Data analysis uses a qualitative approach. After conducting research, the existence of legal innovations in the Syar'iyah Court and guided by Perma Number 3 of 2017 in protecting women's rights can be protected. The Syar'iyah Court has not yet fully given a concrete decision regarding women's rights as a result of divorced divorce by male civil servants. Judges' considerations are gender biased and have a patriarchal mindset, difficulty of execution due to the absence of structural relationship between the court and related institutions to be the reason for the judges to ignore Government Regulation Number 10 of 1983 as amended by Government Regulation Number 45 of 1990 concerning marriage licenses and divorce of civil servants civil. If the regulation has been ratified even though there is no structural relationship and order, the Judge is obliged to carry it out and that the Syar'iyah Court Judge in giving consideration must synergize between the divorce permit in filing the divorce request to court with the decision for civil servants